Adaptation of the land agricultural suitability evaluation system to high-altitude vineyards - Dortzbach, Denilson; Loss, Arcangelo; Pereira, Marcos Gervasio; Machado, Ludmila; Anjos, Lúcia Helena (Revista de Ciencias Agrícolas, 2019)
Adequate information on agricultural land suitability for viticulture are important for the expansion of the activity in wine producing regions, as the state of Santa Catarina, Brazil. This information contributes to improve the efficiency of evaluations, with the inclusion of different management levels for the crop and redefinition of limiting levels of agricultural land conditions. In this context, the objective of this work was to adapt the Land Agricultural Suitability Evaluation System (LASES) to grapevine crops grown in high-altitude regions in Santa Catarina. The LASES was modified based on the crop demands and managements, proposing the incorporation, removal, adjust and update of parameters used in the LASES. The limiting factors considered were topography, fertility, water excess or oxygen deficiency, susceptibility to erosion, impediments to meccanization, and soil effective depth. These traits were based on data of bibliographic surveys and five limiting levels were attributed to them: null, mild, moderate, strong, and very strong. Agricultural suitability classes like good, regular, restrictive and inapt resulted from the interaction between agricultural conditions and management levels of viticulture producers, and later, a suitability guide table was developed. The adaptation of the LASES to grapevine crops grown in high-altitude conditions in Santa Catarina incorporate and adjust local aspects that are important for the grapevine production system. Thus, it is an important tool for decision making when implementing new vineyards and contributes to a possible increase of this activity in the region.